A Biomechanical Evaluation of the Tibia after Retrograde Intramedullary Reaming. Issue 4 (22nd October 2020) - Ciufo, David J.; Koueiter, Denise; Alsaleh, Mariam; Arapovic, Avianna E.; Baker, Kevin C.; Baker, Erin A.; Fortin, Paul T.; Vaupel, Zachary M.
Category: Hindfoot; Ankle; Ankle Arthritis; Basic Sciences/Biologics; Trauma Introduction/Purpose: Autologous bone graft is an important tool in the foot and ankle surgeon's arsenal, and remains the gold standard despite the release of new biologics. The Reamer-Irrigator-Aspirator (RIA) system has become an option for local intramedullary bone graft harvest. Evidence supports the quality of graft and safety of RIA in the femur, and some series have demonstrated its value in tibial reaming for hindfoot fusion. However, there has been no analysis of the mechanical effects of the system on the tibia. The purpose of this study is to investigate the effect of retrograde intramedullary reaming on the mechanical properties of cadaveric tibias, with the hypothesis that this will produce no significant difference in torsional strength between groups. Methods: Intact, fresh frozen tibias were obtained for testing, totaling 11 matched pairs. One tibia was chosen for reaming from each pair with pre-test randomization. The selected tibia was reamed in a retrograde fashion over a guidewire to 12mm, which is the smallest diameter RIA device available. Each tibia was potted and mounted in a custom jig for testing on a servohydraulic test frame. Each specimen was first tested non-destructively for compressive properties using standardized loading rates. Each specimen was then loaded in torsion under constant angular velocity of 9˚/second until failure or the limit of the load cell was reached. Mechanical properties were determined from the load-displacement curve and compared between reamed and unreamed matched pairs using paired samples statistics, with statistical significance set at p=0.05. Results: Specimens were of mean age 56 (range 39-67) years, with 55% being female. The mean compressive stiffness of reamed (560.4 +- 111.7 N/mm) and unreamed (628.2 +- 117.2 N/mm) tibias were not statistically different (p = 0.167). Nine of the reamed specimens and 10 of the unreamed specimens fractured during torsional testing. Torsional testing for stiffness (178.4 Nm/rad +- 59.4 vs 168.1 +- 40.8, p=0.370), rigidity (50.4 Nm2/rad +- 19.1 vs 47.0 +- 13.7, p=0.331), and ultimate load capacity (71.2 Nm +- 24.3 vs 71.9 +- 20.5, p=0.880) showed minimal differences between reamed and unreamed specimens, respectively. Conclusion: Mechanical testing identified no statistically significant differences in torsional or compressive properties of our cadaveric tibias after intramedullary reaming. There was a trend towards decreased compressive stiffness, but this is not a common mechanism of fracture. Our findings suggest that the use of the smallest size RIA system in the tibia does not drastically alter the mechanical properties or require prophylactic fixation. The RIA can be used safely as a method of bone graft harvest or intramedullary debridement in the tibia, as long as appropriate technique is used to avoid eccentric reaming or excessive blood loss.